First record of the leafhopper genus Pedionis (Hemiptera: Cicadellidae: Eurymelinae: Macropsini) from Malaysia with description of a new species - Wang, Dongming; Zhang, Yalin (Zootaxa, 2024)
The genus Pedionis with its species Pedionis (Pedionis) rufoscutellata Huang & Viraktamath, 1993 is recorded for the first time from Malaysia. A new species Pedionis (Pedionis) spiculata sp. nov. is described and illustrated. An updated species checklist with distribution of the genus Pedionis is also provided.